2011
DOI: 10.1016/j.nbd.2011.05.019
|View full text |Cite
|
Sign up to set email alerts
|

The role of CXCR4 signaling in the migration of transplanted oligodendrocyte progenitors into the cerebral white matter

Abstract: Enhancing the ability of either endogenous or transplanted oligodendrocyte progenitors (OPs) to engage in myelination may constitute a novel therapeutic approach to demyelinating diseases of the brain. It is known that in adults neural progenitors situated in the subventricular zone of the lateral ventricle (SVZ) are capable of generating OPs which can migrate into white matter tracts such as the corpus callosum (CC). We observed that progenitor cells in the SVZ of adult mice expressed CXCR4 chemokine receptor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
33
0
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 49 publications
(40 citation statements)
references
References 53 publications
5
33
0
2
Order By: Relevance
“…In addition to regulating the movement of leukocytes, chemokines also control the migration of neural stem cells both during development and in the context of brain disease, where they help to target the migration of neural stem cells to damaged areas of the brain so that they can participate in repair related functions. Hence, interference with chemokine signaling in the brain may have important consequences for both the influx of leukocytes (McCandless et al 2008) and for the migration of OPs during EAE (Banisadr et al 2011). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to regulating the movement of leukocytes, chemokines also control the migration of neural stem cells both during development and in the context of brain disease, where they help to target the migration of neural stem cells to damaged areas of the brain so that they can participate in repair related functions. Hence, interference with chemokine signaling in the brain may have important consequences for both the influx of leukocytes (McCandless et al 2008) and for the migration of OPs during EAE (Banisadr et al 2011). …”
Section: Discussionmentioning
confidence: 99%
“…We have recently shown that chemokines, and SDF-1 in particular, are upregulated in the brain during neuroinflammation and are key factors in regulating the migration of OPs to demyelinated regions in the brains of mice with EAE (Banisadr et al 2011) where OPs can potentially induce remyelination.…”
Section: Introductionmentioning
confidence: 99%
“…Activation of the CXCL12/CXCR7 pathway may also promote oligodendroglial maturation and remyelination in a mouse model of experimental autoimmune encephalomyelitis (EAE) (Gottle et al, 2010). In the EAE model, transplanted OPCs migrated into the injured white matter and differentiated into mature oligodendrocytes via the CXCL12/CXCR4 signaling pathway (Banisadr et al, 2011). Although CXCL12 plays a key role in white matter pathology after stroke, the underlying mechanisms of CXCL12 on oligodendrogenesis after stroke are still largely unknown.…”
Section: Factors Affecting Remyelination After Strokementioning
confidence: 99%
“…Takođe, u životinjskom modelu demijelinizacije indukovane kuprizonom (specifični helator jona bakra), inhibicija CXCR4 ili utiÅ”avanje transkripcije gena za CXCR4 izazvalo je poremećaj diferencijacije prekursora oligodendrocita, onemogućavajući proces remijelinizacije (42). Potvrđena je uloga signalizacije preko CXCR4 i u stimulisanju migracije i aktivnosti prekursora oligodendrocita i prekursora neurona u mozgu životinja sa EAE (43,44,45).…”
Section: Hemokini I Hemokinski Receptori U Cns Tokom Patogeneze Multiunclassified
“…Opadanje nivoa liganda za CXCR3 (CXCL10) detektovano je u serumu pacijenata nakon intravenskog davanja metilprednizolona (91 hemokinom CXCL10 indukovanu migraciju efektorskih CD4+ T-limfocita, in vitro (92). In vitro analizom perifernih T-limfocita kod obolelih od MS utvrđeno je da tretman metilprednizolonom inhibira migraciju ovih ćelija ka CCL19, dok značajno stimuliÅ”e njihovu migraciju ka CXCL12 (93), Å”to ukazuje na pokazane protektivne efekte CXCL12 u patogenezi MS (41,43,44,45). Interferon-Ī² je godinama poznat kao efikasan imunomodulatorni agens za lečenje pacijenata s relapsno-remitentnom MS (94).…”
Section: Uticaj Terapije Na Ekspresiju Hemokina I Hemokinskih Receptounclassified